Landmark-Guided Pudendal Nerve Block versus Penile Block for Postoperative Analgesia in Paediatric Urogenital Surgery: A Retrospective Cohort Study - Eylem Yaşar; Melike Korkmaz Toker (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Postoperative pain control is a fundamental component of optimal perioperative management in patients undergoing paediatric urogenital surgery. Although pudendal nerve block and dorsal penile block are commonly used regional techniques, comparative data—particularly for landmark-guided approaches—remain limited. Therefore, this study aimed to compare the analgesic effectiveness of bilateral pudendal nerve block and dorsal penile block. This retrospective cohort study included children aged 2–10 years who underwent elective urogenital surgery under general anaesthesia between January 2024 and November 2025. Patients were grouped according to the regional block technique documented in the anaesthesia records: bilateral landmark-guided pudendal nerve block (PDB) or penile nerve block (PNB). Postoperative pain was assessed using the FLACC scale in the post-anaesthesia care unit and at 2, 6, 12 and 24 hours. Total paracetamol consumption and rescue analgesia were recorded. Ninety-nine patients were analysed (PDB: 45; PNB: 54). FLACC scores were lower in the PDB group at 6 hours (0.84±1.15 vs 1.72±1.37, p<0.001). Total paracetamol consumption was lower in the PDB group (109.6±73.9 mg vs 188.3±85.4 mg, p<0.001), and fewer patients required rescue analgesia (53.3% vs 74.1%, p=0.03). In this retrospective cohort study, landmark-guided bilateral pudendal nerve block was associated with lower postoperative pain scores at 6 hours and reduced analgesic consumption compared with dorsal penile block in paediatric urogenital surgery.